Knowledge and practices of mothers on home management of diarrhoea in under-fives children at selected primary health care Centre, Rwanda: A descriptive cross-sectional study - Archange Ndayisaba; Adrien Uwizeyimana; Marie Jeanne Tuyisenge; Geldine Chironda (Elsevier, 2022)
Background: Diarrhea remains the main cause of morbidity and mortality in children under 5 years old, accounting for nearly-two million deaths per year globally. Mothers play a significant role in prevention and management of diarrhea related diseases. Aim: The study aimed at assessing the knowledge and practice of mothers on home management of diarrhea in under five children at Ruli health centre in Gakenke district, Rwanda. Methodology: A quantitative non-experimental descriptive cross-sectional design was conducted from April to May 2019. Using simple random sampling, a sample of 160 mothers were selected. Data was collected using a structured interview schedule. Descriptive statistics were used to describe demographics, knowledge, and practice of mothers. Inferential statistics of chi squared, and correlational coefficient (r) were used in identification of significant associations and relationships between demographic factors, mother's knowledge, and practices. Results: Poor knowledge and practices were found in 55.6 % and 52.5 % of mothers, respectively. The diarrhea treatment methods utilized included: using sweetened tea, fruits, drinks, or coffee (76 %), homemade fluids (48.1 %), breast milk, rice drained or clean water and porridge (45 %). Additionally, 31.9 % did not even wash utensils or foods and fruits. Knowledge was significantly associated with both age (p = 0.035); and wealth status (p = 0.033) whilst practice with age (p = 0.002) and a child's caretaker (p = 0.040). There was a strong significant positive linear correlation between practice and knowledge (r = 0.755; p = 0.0001). Conclusion: The mother's knowledge and practice regarding home management of diarrhea was poor. There is need to implement health policy and intensify effective health education approach on home management of diarrhea among mothers with children under 5 years old.